Merck and Vioxx. (A), Should the company continue to battle each of the 27,000 lawsuits filed against it? - Elias, Jaan, (SAGE knowledge. Cases., 2016)
Over the years, Merck & Co. built an enviable reputation not just as a paragon of the pharmaceutical industry but as one of America's most admired businesses. However, after withdrawing its blockbuster drug Vioxx in September of 2004, Merck found its reputation and its financial stability in danger. The day after the announcement, Merck's stock plunged 30% and a few analysts even wondered if Merck would be forced into bankruptcy. This study looks at the processes that Merck would need to go through before achieving stability.